Faktor-faktor Penentu Ketidakteraturan Berobat Penderita Kusta dl Yogyakarta Tahun 2002:: Determining Factors of Pursuing Treatment Irregularity among Leprosy Patients in Yogyakarta in 2002 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The release from treatment of leprosy cases were very determined by their compliance to the treatment schedule, This study was aimed at finding determining factors of treatment irregularity among leprosy patients in Yogyakarta in 2002. The study was a case-control study. The locations were regencies of Bantul, Sleman, Gunung Kidul, and Yogyakarta as those areas had many leprosy patients. The subjects were 62 leprosy patients who still got treatment, finished getting treatment, or RFT in public health centers and Dr. Sardjito Hospital. The subjects consisted of 32 cases (un comply) and 30 cases (compliy) as control. The result showed that the bivariate analysis showed there were some statistically significant risk factors, i.e. male OR=0.79 (95% CI: 1.07-14.00)